Study on the Underwriting Circle of Property-Liability Insurance Market under Competition - Wang, Yunpeng (Advances in Social Sciences Research Journal, 2017)
The paper models the competition between non-life insurers within the framework of game theory and solve the Nash equilibrium with software R. The dynamic game where insurers compete in multiple periods shows the characteristic of underwriting cycle, which has been tested in the non-life insurance markets of many countries. Whereas the theoretical explanation for the existence of underwriting cycle is not settled, the paper contributes an additional explanation. With 1000 simulations of the dynamic game, shows the . The length of the underwriting cycle is distributed in 7 to 8 years.